3D reconstruction of human face from an input image under random lighting condition. (2018) - Sun, Yujuan; Zhang, Xiaofeng; Jian, Muwei
The three-dimensional reconstruction from single input image is quite difficult due to many unknown parameters, such as the light conditions, the surface normal and albedo of the object. However, there are overall similar characteristics for different human faces, such as the shapes and the positions of the eyes, nose; mouth and ears are generally identical. The similar characteristics has been used in this paper to relax the numbers of the input face images, and reconstruct the 3D shape based on a couple statistical model. Moreover, the light condition of the single input image can be different from that of training database. The experiment results show the effectiveness of the proposed method.